2021
DOI: 10.3389/fpsyg.2021.741563
|View full text |Cite
|
Sign up to set email alerts
|

Job Demands and Resources, Burnout, and Psychological Distress of Social Workers in China: Moderation Effects of Gender and Age

Abstract: Social work is a fast-growing profession in China, with the workforce numbering approximately 1.2 million in 2018. Studies have shown, however, that social workers in China experience high burnout rates and significant psychological distress. Analyzing data collected from 897 social workers in Chengdu, China, we applied the job demands and resources (JD-R) theory to examine the effects of JD-R on burnout and psychological distress in social workers, as well as whether these relations are moderated by gender an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…In 2013, the Shenzhen social worker turnover rate was over 22% ( Du, 2015 ). Additionally, using the Maslach Burnout Inventory (MBI) to measure burnout amongst social workers in China, various studies have found the average burnout was 53.9 out of 102 in Chengdu ( Xie et al, 2021 ), and was 56.6 in Guangzhou ( Wang et al, 2019 ). These two Chinese cities’ burnout levels appear to fall in the middle of international range.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2013, the Shenzhen social worker turnover rate was over 22% ( Du, 2015 ). Additionally, using the Maslach Burnout Inventory (MBI) to measure burnout amongst social workers in China, various studies have found the average burnout was 53.9 out of 102 in Chengdu ( Xie et al, 2021 ), and was 56.6 in Guangzhou ( Wang et al, 2019 ). These two Chinese cities’ burnout levels appear to fall in the middle of international range.…”
Section: Introductionmentioning
confidence: 99%
“…Increased burnout and turnover rates will generally impose negative consequences on not only the field of social work, but also on its labor force and its client populations ( Social Work Policy Institute, 2010 ; Child Welfare Information Gateway, 2016 ; Casey Family Programs, 2017 ). For example, social workers who experience burnout may be unable to maintain quality client services, which can create harm, especially to their more vulnerable clients ( Hamama, 2012 ; Casey Family Programs, 2017 ; Xie et al, 2021 ). Additionally, high turnover rates may force agencies to become understaffed and thus social workers who remain in the labor force are working with increased job demands and workloads ( Yürür and Sarikaya, 2012 ; Child Welfare Information Gateway, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Capone and Petrillo ( 31 ) found job burnout was significantly linked to depression ( r = 0.42) amongst a sample of 285 high school teachers. Likewise, Xie et al ( 35 ) found burnout significantly increased psychological distress (Beta = 0.46) amongst a sample of 897 social workers based in Chengdu, China. Thus, burnout is an important factor of health outcomes for social workers, as well as other professionals in China and beyond ( 28 , 30 , 32 , 34 , 35 ).…”
Section: Introductionmentioning
confidence: 92%
“…Additionally, task performance measures the employee's success at delivering specific work outcomes, as well as quality and quantity work (48,49). It is critical to examine burnout, work engagement, and task performance through the lens of JD-R Theory (11,21,39) as numerous researchers have discovered JD and JR have direct effects on task performance, as well as indirect effects through burnout and work engagement (18,21,35,38). Task performance is negatively affected by JD and burnout (50)(51)(52)(53).…”
Section: Task Performancementioning
confidence: 99%
See 1 more Smart Citation